HEMATOLOGICAL DISORDERS IN LIVER CIRRHOSIS: MODERN CONCEPTS OF PATHOGENESIS, DIAGNOSTICS, AND CLINICAL SIGNIFICANCE IN THE CONTEXT OF THE REBALANCED HEMOSTASIS CONCEPT (International journal of medical sciences, 2025)
Liver cirrhosis is a chronic progressive disease accompanied by profound morphological and functional alterations of the hepatobiliary system. Hemostatic disorders represent a characteristic component of cirrhosis and include anemia, thrombocytopenia, leukopenia, and coagulopathy. Contemporary research demonstrates that the hemostatic system in cirrhosis is not in a state of complete hypocoagulation, as previously believed. Instead, a condition of “rebalanced hemostasis” develops, in which impaired production of procoagulants and anticoagulants maintains a fragile equilibrium, predisposing patients to both bleeding and thrombosis. This article summarizes current data on the mechanisms of hematological disorders, diagnostic approaches, and therapeutic strategies, including discussion of the roles of thrombopoietin, hepcidin, coagulation factors, hypersplenism, and portal hypertension. Understanding these processes is essential for optimizing patient management and guiding treatment decisions.